Analisis Proses Bisnis Penerbitan Kartu Pengawasan Menggunakan Pendekatan Deskriptif Kualitatif - Jamaludin, Ahmad; Supriadi , Fidi; Junaedi , Dani Indra (Jurnal Informatika, Multimedia dan Teknik, 2024)
Information technology has become a crucial component that influences and changes business processes in modern organizations. The application of information technology can increase efficiency and productivity through increasing speed, accuracy and collaboration in business processes. This technology also drives innovation, competitive advantage, and better and more responsive service. The Sumedang Regency Transportation Service, as a regional government agency, has a service function, namely issuing supervision cards. However, currently, the process of issuing Kartu Pengawasan still takes a relatively long time, making it less effective and efficient with ongoing business processes. This research aims to analyze the business process of issuing Kartu Pengawasanat the Sumedang Regency Transportation Service using a qualitative descriptive research method. This analysis is expected to identify deficiencies and opportunities for improvement in the publishing process, so that services can be implemented more effectively and efficiently. And can also provide recommendations for implementing new business processes by utilizing information technology.